A note on commuting times and city size: Testing variances as well as means - An, Qian; Gordon, Peter; Moore, James E. (Journal of Transport and Land Use, 2014)
Relatively little attention has been paid to the relationship between commute time variances and city size. In this paper, we utilize 2009 Nationwide Highway Travel Survey data and test the relationship between area commute-time means as well as variances in metropolitan-area size. We include tests for metropolitan areas as a whole and for residents from urban, suburban, second city, and town-and-county areas. The regression analysis shows that all estimated slopes are statistically significant but not much greater than zero. Commute time means and variances are highly correlated. These relationships are also invariant with respect to the place of residence. An extensive collection of literature provides evidence for the co-location of workers and jobs hypothesis: average commute times do not rise appreciably as metropolitan population increases. We conclude that these results are additional, although indirect, evidence for the co-location hypothesis.